Gambaran Tingkat Pengetahuan dan Perilaku Penderita Penyakit Hipertensi di Puskesmas Kecamatan Rawamerta Kabupaten Karawang Tahun 2021 - Mohamad Malik Aziz Ali ajazi; Arifin S; Pritha P (Syntax Corporation, 2023)
Hypertension is a disease that often arises and even becomes a big challenge in Indonesia and is often found in health services. The success of preventing hypertension recurrence can be seen from the attitudes and knowledge of clients who have a history of hypertension. This study aims to determine the picture of knowledge and behavior of hypertension prevention at the Rawamerta health center, Karawang Regency. Method: This study used a cross-sectional descriptive research design Measurement of knowledge and behavior in this study using questionnaire sheets, using Likert scale. The sampling technique used simple random sampling and obtained the number of samples in this study was 87 respondents at the Rawamerta health center, Karawang Regency. Results: Based on the results of this study showed that the level of knowledge was high (77.0%) while the least knowledge was low (23.0%). Meanwhile, for good behavior (63.2%) and having bad behavior (36.8%).